Phenotype-genotype correlation in multiple primary lung cancer patients in China - Yang, Yang (Sci Rep, 2016)
Due to recent advances in high-resolution detection technology, multiple primary lung cancer (MPLC) is becoming an increasingly common diagnosis. However, the genotype-phenotype correlations in MPLC patients have not yet been assessed. In this study, we analyzed the clinical and pathological data for 129 consecutive MPLC patients who received curative surgery at the Tongji University Shanghai Pulmonary Hospital, China. We have screened 129 patients in the present study and found mutations in EGFR, BRAF, ROS1 and KRAS genes, as well as the rearrangement of the EML4-ALK gene in 113 patients. The mean patient age was 59.9 (25–78) years old and 41 patients were males (31.8%). Among the total patients, 123 (95.4%) had two primary lesions, 5 (3.9%) had three primary lesions, and 1 (0.8%) had four primary lesions. In 38.8% of the patients, all lesions were located on only one side of the body. Most of the detected mutations (98 patients) were in the EGFR gene. The patients exhibited significant differences in the EGFR mutation, age at diagnosis, and foci location.